Characteristics and dynamics of extreme winters in the Barents Sea in a changing climate - K. Hartmuth; H. Wernli; L. Papritz; L. Papritz (Weather and Climate Dynamics)
The Barents Sea is experiencing large declines in sea ice and increasing surface temperatures while at the same time it is a key region of weather variability in the Arctic. In this study, we identify extreme winter seasons in the Barents Sea, based on a multivariate method, as winters with large seasonal anomalies in one or several surface parameters encompassing surface temperature, precipitation, surface heat fluxes, and surface net radiation. The analyses are based on large-ensemble climate model data for historical (S2000) and end-of-century (S2100) projections following an RCP8.5 emission scenario. In the phase space of the considered seasonal-mean surface weather parameters, we find distinct clusters of extreme winters that are characterized by similar combinations of anomalies in these parameters. In particular, during extreme winters in S2000 simulations, anomalies in surface air temperature during extreme seasons tend to be spatially extended with their maximum amplitude over sea ice. This maximum shifts towards the continental land masses in a warmer climate (S2100), as the formation of intense warm or cold anomalies is damped by the increasing area of open ocean. Our results reveal that large anomalies in surface parameters during extreme seasons are characterized by distinct patterns of anomalous frequencies in cyclones, anticyclones, and cold air outbreaks because these weather systems are responsible for temperature and moisture advection, the formation or suppression of precipitation, and intense surface fluxes. We further show that anomalous surface boundary conditions at the beginning of a season – that is, sea ice concentration and sea surface temperatures – facilitate the formation of persistent anomalous surface conditions or further enhance atmospherically driven anomalies due to anomalous surface heat fluxes. However, a decrease in the variability of both sea ice and sea surface temperatures in S2100 indicates a decreasing importance of anomalous surface boundary conditions for the formation of future extreme winters in the Barents Sea, while the robust link shown for surface weather systems persists in a warmer climate.